Efficacy and Safety of Antihypertensive Drugs in Chronic Kidney Disease Patients at Menggala Regional General Hospital - Denny Ardhianto; Made Laksmi Meiliana; Dwi Ismayati; Syaripah Ulandari; Okta Puspita; Rena Oktaviana (Universitas Wahid Hasyim Semarang, 2026)
Chronic kidney disease (CKD) is a progressive condition characterized by a gradual decline in glomerular filtration rate, often accompanied by hypertension, necessitating antihypertensive therapy. This study aimed to evaluate the effectiveness of antihypertensive drugs in achieving blood pressure targets (<140/90 mmHg or a mean arterial pressure reduction of ≥20 mmHg) and to identify the incidence of adverse effects in CKD patients at Menggala Regional General Hospital during 2024. A retrospective observational study was conducted using medical records from 199 CKD inpatients selected via purposive sampling. Data analysis employed descriptive statistics, paired t-tests for effectiveness, and chi-square tests for associations between drug types. Results indicated that combination therapy with furosemide IV, candesartan, and amlodipine was the most common (77.4%) and demonstrated effectiveness in 50.8% of cases (p=0.01). Adverse effects occurred in only 1.0% of patients, primarily peripheral edema. The findings underscore the efficacy of combination therapies involving diuretics, ARBs, and CCBs in managing hypertension in CKD, with minimal adverse events. This research provides valuable insights for optimizing antihypertensive regimens in similar settings.